Take the 2-minute tour ×
MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

What do you use to prove the following equality (and possibly more general ones of the kind)?

\begin{align*}\sum_{r,s,t} \frac{q^{r^2+rs+s^2+st+t^2}}{(q)_r (q)_s (q)_t} z_1^{r+s} z_2^{s+t} = \sum_{a,b} \frac{q^{a^2-ab+b^2}}{(q)_a (q)_b} z_1^a z_2^b \end{align*}

Thanks!

share|improve this question
    
I know it should be easy to prove it, but I am trying to pin down the simplest way to do it. It is mentioned on pg 28 of arxiv.org/pdf/hep-th/9308079.pdf. Since I am not an expert in the field, I was hoping I could get a hint from some of you... –  Andrew Jun 26 '12 at 20:01
2  
You might want to start with 2.3.2 in my survey: math.ucla.edu/~pak/papers/psurvey.pdf –  Igor Pak Jun 27 '12 at 0:02
add comment

2 Answers 2

I keep the notation $(q)_s=\prod_{i=1}^s(1-q^i)$, and in addition set \begin{equation}\binom{a}{s}_q=\frac{(q)_a}{(q)_s(q)_{a-s}},\end{equation}the Gaussian binomial coefficient.

Comparing coefficients, the question amounts to showing that \begin{equation} \sum_s\binom{a}{s}_q\binom{b}{s}_q(q)_sq^{(a-s)(b-s)}=1. \end{equation}

This, however follows immediately from induction over $a$: The assertion is obvious for $a=0$. Now suppose $a\ge1$. Use \begin{equation} \binom{a}{s}_q=q^s\binom{a-1}{s}_q+\binom{a-1}{s-1}_q \end{equation} to replace $\binom{a}{s}_q$. The contribution from the first summand of the right hand side gives $q^b$ (I omit the trivial calculation), by applying the induction hypothesis to $a-1$. In order to handle the contribution from the second summand, we note that \begin{equation} \binom{b}{s}_q(q)_s=(1-q^b)(q)_{s-1}\binom{b-1}{s-1}_q. \end{equation} So, applying the induction hypothesis for $a-1$ once again, we see that this other contribution is $1-q^b$. Now $q^b+(1-q^b)=1$ yields the result.

share|improve this answer
add comment

Actually, I believe the generating functions are in fact not equal. They differ on the coefficient for $z_1 z_2$. The left-hand side is $1+z_1+z_2+2z_1 z_2 + \cdots$, and the right-hand side is $1+z_1+z_2+z_1 z_2 /q + \cdots$ (this is assuming you start the running variables all at 0; starting some of them at 1 doesn't fix this inequality).

share|improve this answer
    
I don't see how: e.g. r+s=1 and s+t = 1 gives r=0, s=1, t=0, and r = 1, s=0, t=1, which leads to \frac{q}{(q)} + \frac{q^2}{(q)^2}, which is the same when you take a=1 and b=1 and calculate the corresponding coefficient –  Andrew Jun 27 '12 at 11:58
    
I agree with your calculation for the coefficient on the LHS (which simplifies to just $\frac{q}{(q)} + \frac{q^2}{(q)^2} = 1 + 1 = 2$). But as I said, the RHS coefficient (for $a=b=1$) is $q^{1-1+1}/(q)^2 = q/q^2 = 1/q$. There's a fine chance that I'm doing something quite stupid, in which case, let me know! –  Pat Devlin Jun 27 '12 at 14:08
    
OK, i understand now - in my notation $(q)_a$ means $\prod_{i=1}^{a}(1−q^i)$. Sorry for not clarifying... – Andrew 0 secs ago –  Andrew Jun 27 '12 at 14:16
    
Ah! I had guessed it was the Pochhammer symbol. –  Pat Devlin Jun 27 '12 at 14:26
4  
Andrew: perhaps edit your original question too to clarify the notation, so that other readers aren't confused. –  Zsbán Ambrus Sep 5 '12 at 16:54
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.